(untitled) (Research, Society and Development, 2020)
This study aimed to investigate the typical sensory characteristics of artisanal cheeses produced in the micro-region of Araxá - MG through Quantitative Descriptive Analysis (QDA) since there are few studies on the sensory profile of this type of cheese. The survey of the sample descriptors was carried out by previously selected panelists. The samples were subjected to a sensory acceptance test with untrained panelists to analyze the attributes appearance, aroma, texture, flavor, and overall acceptance. The acceptance test was carried out using a 9-point hedonic scale. The physicochemical characterization of the cheeses was also performed by the determination of fat content, protein, moisture, ash, and sodium chloride levels, as well as the texture profile analysis, using a TA.XT2 texture analyzer. According to the sensory panel, the cheeses exhibited pale-yellow color, which was more prominent in the rind, great firmness, and a tendency to brittleness, high moisture, low number of eyes, characteristic aroma tending to strong odor, excessive acid taste, and low salty taste. The cheeses had good sensory acceptance by the untrained panelists. The physicochemical results corroborated those found in the literature. Regarding the texture profile, few studies have assessed of artisanal Minas cheese, thus further studies should be encouraged to better investigate the changes in the texture profile of the cheeses.